The benzodiazepine consumption by elderly women - Mendonça, Reginaldo Teixeira; Carvalho, Antonio Carlos Duarte de (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2005)
Benzodiazepines are some of the most frequently consumed drugs, especially by elderly women. Through semi-structured interviews with 18 elderly women who were psychiatric patients attended at the Mental Health Centre of the FMRP-USP School Health Centre, we aimed to show their concepts on benzodiazepines and show the interaction among biological, social and cultural factors involved in this dependence. We concluded that, according to the participants concepts, benzodiazepine consumption and dependence are singular and are not restricted to a biological relation between benzodiazepine effects, but include the influence of cultural and social factors.